Crises of Science - Slavėnas, Paulius (Problemos, 1969)
Temporary delays in the development of science caused by incongruity between facts and routine school notions are viewed in the paper from the historical scientific angle. The overall character of conclusions accounts for viciousness of the notions which found their relative .justification in early stages of knowledge as well as for their converting into hindrance of science. Facts contradicting prejudices are ignored for long, then they manifest themselves as paradoxes and, finally, after a collapse of routine categories, make the basis of new theories. The paper presents the following historical review: the false conception of inert matter in respect to which energy and motion is something instilled, too absolute treatment of the states of substance (their misinterpretation as substances), difficulties in comprehending the relativity of motion, a long time mistrust towards optical means for investigation of nature, centuries-old belief in the possibility of constructing the overall geometry by logical reasoning irrelevantly to physical experience. To have the relativity theory established the overgeneralization of simultaneity had to be overcome. The routine notion of the Universe as non-evolving proofs bard to conquer. This refers as much lo the autonomy conception of physical processes, i.e., the principal independence of the surrounding Cosmos. Comprehension of quantum physics is impeded by excessively general coupling of the notions of uniqueness and of self-identity.